Harmonization of Islamic Knowledge: Perception of the Importance of Integration of Knowledge in Islam - Nisa, Zahrotun; Amrillah, Rizki; Safarudin, Safarudin; Tussoleha, Dhea (Jurnal Riset Ilmu Pendidikan, 2025)
This study discusses the importance of harmonizing Islamic knowledge through the integration of religious knowledge and modern knowledge in facing global challenges. Through a literature study approach, this study explores the concept of integration developed by M. Amin Abdullah and the contributions of thinkers such as Syed Muhammad Naquib al-Attas and Ismail Raji al-Faruqi. The results of the study show that the integration of knowledge not only strengthens the understanding of Islamic teachings but also creates synergy with modern knowledge to produce more holistic solutions to various issues, including education, community development, innovation, and welfare. This harmonization encourages collaboration between academics, scholars, and the community to ensure the relevance of Islamic values ??in the contemporary context. This study emphasizes the need for an interconnected approach that integrates various disciplines in order to create a more harmonious and balanced society.